The Effect of Ratio of Gom Arabic and Caragennan and Cooking Time on The Quality of Passion Fruit Jelly - Dimas Iwanda; Zulkifli Lubis; Mimi Nurminah (Universitas Sumatera Utara, 2016)
The purpose of this study was to determine the effect ratio of gom arabic and carragenan and cooking time on the quality of passion fruit jelly. This study used completely randomized design with two factors, ie: ratio of gum arabic and caragennan (P) (100%:0%, 75%:25%, 50%:50%, 25%:75%, and 100%:0%) and cooking timen (L): (10 minutes, 15 minutes, and 20 minutes). The analyzed parameters were moisture content (%), ash content (%), total soluble solid (oBrix), vitamin C content (mg/100g), total acid (%), total plate count (CFU/g), sensory test (color, flavor, taste, and plasticity). The ratio of gum arabic and carragenan gave highly significant effect on moisture content, ash content, and sensory test of flavor and plasticity. Cooking time gave highly significant effect on moisture content, ash content, total soluble solid, total acid, sensory test of colour, and taste, and gave significant effect on sensory test of flavor. The interaction of the ratio of gom arabic and caragennan and cooking time had highly significant effect to ash content and sensory test of plasticity, and gave significant effect on moisture content and total soluble solid. The ratio of gom arabic and carragenan 25%:75% with 10 minutes cooking time produced the best passion fruit jelly. Keywords: Carragenan, cooking time, gom arabic, jelly, passion fruit.